Silica-based Photonic Crystal Fiber for Supercontinuum Generation in the Anomalous Dispersion Region: Measurement and Simulation - Chu, Van Bien; Le, Hieu Van; Hoang, Van Chin; Nguyen, Thi Thao; Hoang, Van Thuy; Ho, Dinh Quang; Cao, Long Van (Communications in Physics, 2022)
We report on numerical simulation and experimental study of the supercontinuum (SC) generation in the anomalous dispersion region of photonic crystal fiber (PCF). The results show that a flat and stable spectrum with bandwidth of 130 nm around the central pump wavelength was achieved with an input power of 4.0 W. Although the measured spectrum is slightly different from the numerical ones, a good consistency can be recognized in the major sideband positions and spectral width. In addition, the chromatic dispersion of air silica PCF was measured at visible and near-infrared wavelengths using the Mach-Zehnder interferometer configuration and then verified by comparison with simulated results.